Investigating the effect of silver nanoparticles on carbon dioxide hydrates formation. (December 2018) - Nashed, Omar; Youssouf, Sadadine Mahamat; Sabil, Khalik M.; Shariff, Azmi Mohd; Sufian, Suriati; Lal, Bhajan
Abstract: Gas hydrates have been considered as a promising approach for gas separation, storage, and transportation. Low hydrates formation rate has been identified as a major weakness of this technology. However, introducing hydrate promoter could accelerate the hydrates formation process. In this paper, silver nanofluids are investigated as kinetic CO2 hydrates promoter by measuring the induction time, the initial rate of CO2 hydrate formation, and the amount of CO2 gas consumed at a pressure of 2.7MPa and temperature of 277.15 K. Silver nanofluids are prepared at a concentration range of 0.01 to 0.1 wt% of silver nanoparticles mixed with 0.08 SDS wt%. The experiments are conducted through high pressure reactor hydrate cell. The results show that nanoparticles enhance the initial hydrate formation rate and amount of gas consumption. However, no significant effect is observed on the induction time compared to SDS solution.